Hubungan Pengobatan Antiretroviral dengan Stres pada Orang Dengan HIV/AIDS Di Rumah Singgah X Kota Jayapura Tahun 2016 - Mina Blandina Ayomi (Jurnal Promosi Kesehatan Indonesia, 2017)
Background: Stress that occurs in individuals will impact on the emergence of problems related to health, psychology and interpersonal interaction. In a physical disorder a person experiencing stress will be susceptible to disease, the mental disorders of prolonged stress will cause tension, it will damage the body and health problems. In interpersonal disorders stress will be more sensitive to loss of self-confidence, withdrawal and others. The support gained by PLWHA can be used as a coping or survival effort, as HIV / AIDS is not the end of everything, with good coping owned by PLWHA will be very helpful in antiretroviral treatment adherence and continue its life.Method: The type of research used is Explanatory Research, The time of the research will be done in September Year 2016 and the location of the research was conducted four shelters Surya Kasih Kota Jayapura. The sample in this research there are 33 responder. The way used in data retrieval in this study is to use questionnaires that are filled by respondents.Results: The results showed that the age of 27-30 years 11 respondents (31.3%), male gender 18 respondents (54.5%), mode of transmission through sex 28 respondents (84.8%), ARV treatment drink 31 of respondents (93.9%), there is a relationship between ARV treatment with stress in people with HIV AIDS in Jayapura shelter home with p-value value 0.001.Keywords: ARV Treatment, Stress, People With HIV / AIDS